Analysis of the accounting speciality collage graduates’ employment opportunities at the labour market in the context of the workforce supply and demand - Bagdonienė, Audronė; Smolenskienė, Fausta (Buhalterinės apskaitos teorija ir praktika, 2014)
The problems which young people face with in order to get employed and survive, to compete successfully in the labour market has always been relevant to the society. It is obvious that after the completion of the training institutions the graduates can hope to get employed if their specialty is in high demand in the labour market. Permanent labour market demand and supply indicators are monitored and analysis allows to foresee the changes of the tendencies and trends to find out which specialty is needed most and have the most job opportunities in the world of work. Therefore, the research problem is revealed by the following questions: What are the opportunities to get employed having accounting profession? Are the people, gained such education, in demand in the labour market? The aim of the investigation – to evaluate the accounting specialty graduates’ employment opportunities in the labour market. Youth situation in the labour market is not favourable, and still significant positive changes still are not visible, because in recent years in recent years there at the labour centre applied approximately 70 thousand young people under 25 and about 20 thousand graduates. However, an analysis of the need for accounting professionals and graduates who have acquired the specialty of integration into the labour market statistics show that the demand for these professionals is not decreasing. As pointed out by some labour market analysts, this is one of the most stable professions and such individuals have significant employment opportunities in this field. This is also confirmed by the results of analysis: every year, employers offer about 2-3 thousand jobs for accountants and book-keepers; there are favourable employment opportunities in all regions of the country, as more and more businessmen are choosing financial services companies receive all levels of accounting services; every year graduates, who have acquired the specialty, number is decreasing, so the competition is to prepare professionals in the labour market is weakening; vacancy rate remains stable (on average by 0.6 per cent.), excess supply in the market for these professionals is not high, i.e. 2 persons apply for 1 vacancy.